Metode Pembelajaran Latihan (Drill) dalam Meningkatkan Hasil Belajar Pembuatan Konstruksi Pola Dasar Badan Wanita Sistem Porrie pada Kelas XI Busana SMKN 2 Jombang. - Dewi, Tantri Kusuma (Universitas Negeri Surabaya, 2020)
Methods off drill is to teach by providing that students need to learn to acquiree a particulare skills. Student can not directly make a female body pattern correctly using Porrie system, but the exercises are needed starting from learning the step of making patterns, making body pattern lines, adjusting body pattern using 1: 4 scale. in SMKN 2 Jombang there are obstacles in class XI students in the 2018/2019 school year students lack understanding in making Porrie system body patterns because when class X the pattern construction lesson uses the KTSP curriculum in accordance with the lesson plans given by the teacher is making a practical system body pattern. This Porrie system has a higher level of difficulty and complexity than making practical system patterns. The research objective was to determine whether there was an increase in student learning outcomes in the construction of the Porrie system women's archetypal construction. The method used in this research is Classroom Action Research (CAR) or Classroom Action Research (CAR). The experiment was conducted in SMKN 2 Jombang in class XI Clothing 2 were 31 students. Data collection through pre-test and post-test with 4 stages of data collection in every 20 minutes of learning. The result showed by average increased of 13,7% from exercise phase 1 to exercise phase 2, 5,3% from exercise phase 3 to exercise phase 4. Based on classical completeness there was a significant of 70,8% from phase 1 to phase 4. (with KKM result 70 individual completeness and 70% classical completeness). Keywords : Learning methods drill, student learning